The hyperexcitability of dentate granule neurons in organotypic hippocampal slice cultures is due to reorganization of synaptic inputs in vitro - Gilbride, Charlie J. (Physiol Rep, 2016)
Organotypic hippocampal slice cultures (OHSCs) provide the experimental flexibility of cell culture while leaving much of the natural neuronal connectivity intact. Previously, it was shown that the functional and morphological features of CA1 pyramidal neurons in OHSCs resemble, to a surprising extent, those of CA1 neurons in the acute brain slice preparation. However, the extent to which the characteristics of other principle hippocampal neurons change or are preserved in cultured slices remains to be determined. In the present study, I initially sought to understand whether and how the synaptic inputs and morphology of cultured dentate granule neurons (GCs) differ from GCs that have developed in vivo. To this end, I compared GCs in OHSCs and GCs in acute slices at two equivalent developmental time points (P14 vs. DIV7 and P21 vs. DIV21). The findings suggest that there is considerable reorganization of synaptic input to the organotypic GCs, such that these cells are more susceptible to hyperexcitation than GCs in acute slices after 3 weeks. It appears that this hyperexcitability emerges through an increase in the proportion of mature synapses at proximal dendritic sites and is accompanied by an increase in inhibitory neuron activity. These alterations appear to arise in a coordinated manner such that the substantial increase in excitatory synaptic drive received by the DIV21 GCs in OHSCs remains local and is not translated into excessive output possibly leading to damage or major morphological alterations of downstream pyramidal neurons.